2021
DOI: 10.1016/j.bja.2021.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative lymphopaenia, mortality, and morbidity after elective surgery: systematic review and meta-analysis

Abstract: Background: In the general adult population, lymphopaenia is associated with an increased risk for hospitalisation with infection and infection-related death. The quality of evidence and strength of association between perioperative lymphopaenia across different surgical procedures and mortality/morbidity has not been examined by systematic review or meta-analysis. Methods: We searched MEDLINE, Embase, Web of Science, Google Scholar, and Cochrane databases from their inception to June 29, 2020 for observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…[6] Pre-operative lymphopenia is associated with a higher incidence of post-operative complications such as cardiac, infectious, and renal failure. [7] In the general population, lymphopenia is also associated with an increased risk of hospitalization for infection. [7] The level of albumin in serum is considered an indicator of nutritional status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Pre-operative lymphopenia is associated with a higher incidence of post-operative complications such as cardiac, infectious, and renal failure. [7] In the general population, lymphopenia is also associated with an increased risk of hospitalization for infection. [7] The level of albumin in serum is considered an indicator of nutritional status.…”
Section: Introductionmentioning
confidence: 99%
“…[7] In the general population, lymphopenia is also associated with an increased risk of hospitalization for infection. [7] The level of albumin in serum is considered an indicator of nutritional status. Albumin that is a negatively charged substance synthesized by the liver is an acute-phase reactant.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphopenia has been associated with increased mortality and infection risk in a wide range of settings including community populations, perioperative, and sepsis [ 15 , 18 , 19 , 45 ]. The studies have broadly shown that lymphopenia is associated with an increased risk of infections and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are broadly in line with other studies. In a meta-analysis of peri-operative patients, lymphopenia was associated with a three-fold increase in mortality and a higher rate of postoperative complications and infections [ 45 ]. While we demonstrated increased mortality in both ‘early’ and ‘late’ deaths, we did not demonstrate an increase in risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that lymphopenia is one of the typical phenotypes of immune dysregulation and is among the strongest risk factors for outcomes in cardiovascular and noncardiovascular disorders [16][17][18][19][20][21]. However, the relationship between lymphopenia and AAD mortality has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%